Fertility preservation for pediatric patients with hemoglobinopathies: Multidisciplinary counseling needed to optimize outcomes - Bedrick, Bronwyn S.; Kohn, Taylor P.; Pecker, Lydia H.; Christianson, Mindy S. (Frontiers in Endocrinology, 2022)
Hemoglobinopathies are autosomal recessive disorders that occur when genetic mutations negatively impact the function of hemoglobin. Common hemoglobinopathies that are clinically significant include sickle cell disease, alpha thalassemia, and beta thalassemia. Advancements in disease-modifying and curative treatments for the common hemoglobinopathies over the past thirty years have led to improvements in patient quality of life and longevity for those who are affected. However, the diseases, their treatments and cures pose infertility risks, making fertility preservation counseling and treatment an important part of the contemporary comprehensive patient care. Sickle cell disease negatively impacts both male and female infertility, primarily by testicular failure and decreased ovarian reserve, respectively. Fertility in males and females with beta thalassemia major is negatively impacted by iron deposition due to chronic blood transfusions. Hematopoietic stem cell transplant (HSCT) is currently the only curative treatment for SCD and transfusion dependent beta thalassemia. Many of the conditioning regimens for HSCT contain chemotherapeutic agents with known gonadotoxicity and whole-body radiation. Although most clinical studies on toxicity and impact of HSCT on long-term health do not evaluate fertility, gonadal failure is common. Male fertility preservation modalities that exist prior to HSCT include sperm banking for pubertal males and testicular cryopreservation for pre-pubertal boys. For female patients, fertility preservation options include oocyte cryopreservation and ovarian tissue cryopreservation. Oocyte cryopreservation requires controlled ovarian hyperstimulation (COH) with ten to fourteen days of intensive monitoring and medication administration. This is feasible once the patient has undergone menarche. Follicular growth is monitored via transvaginal or transabdominal ultrasound, and hormone levels are monitored through frequent blood work. Oocytes are harvested via a minimally invasive approach under anesthesia. Complications of COH are more common in patients with hemoglobinopathies. Ovarian hyperstimulation syndrome creates a greater risk to patients with underlying vascular, pulmonary, and renal injury, as they may be less able to tolerate fluids shifts. Thus, it is critical to monitor patients undergoing COH closely with close collaboration between the hematology and the reproductive endocrinology teams. Counseling patients and families about future fertility must take into consideration the patient’s disease, treatment history, and planned treatment, acknowledging current knowledge gaps.